(untitled) (Scientific journal of the Fergana State University, 2023)
This article focuses on the meaning of rhetorics as a science of the art of eloquence, as a science of thought and speech. Rhetorical speech contains its own specific canons of speech construction, provides an opportunity to practically master perfect speech, teaches how to speak correctly, express your thought, organize speech communication, create new forms of expressing your own statements, which is important and necessary to teach young people who seek to improve themselves and learn new things.